Beyond Mind and Body: Embodied Intelligence in Young Children's Creative Dance Experiences - Ujang Maulana Yusup; Juju Masunah; Rita Milyartini; Mubiar Agustin (Perkumpulan Pengelola Jurnal (PPJ) PAUD Indonesia, 2026)
This study aims to explore how embodied intelligence emerges through children's involvement in creative dance activities at an early childhood education institution in Indonesia. The study used a qualitative case study approach involving 20 children aged 4–5 years, two classroom teachers, and one school administrator at KB Al Fathu, Bandung City. Data were obtained through participant observation, video recording, semi-structured interviews, and reflective conversations with the children, then analyzed using reflexive thematic analysis. The results show that embodied intelligence develops through four interconnected dimensions: body awareness, the ability to express emotions through movement, the ability to coordinate actions with others, and the ability to construct meaning through bodily experiences. These four dimensions do not emerge as stand-alone abilities, but develop in an integrated manner as children move, interact, and give meaning to their experiences. Based on these findings, this study proposes embodied intelligence as a conceptual framework that connects embodied cognition, embodied pedagogy, and creative dance to explain how holistic learning occurs in early childhood education.